Quality inspection management on construction site / Hamizah Hairum - Hairum, Hamizah (Faculty of Architecture, Planning and Surveying, 2010)
Inspection on the site is important to control the quality and quantity of work at construction sites. The objectives of this dissertation is to identify the process and method of quality inspection management being held in construction site and highlight the common problem and obstacle during the implementation while identify the solution in preventing the problem or obstacle on carry out the inspection during construction process. There are several differences between the inspection process and method for private projects to government projects. But basically, the same inspection method used in the implementation of quality inspection management on construction site. The commonly problem that occur are about managing the flow of inspection process and the documentation on site. In addition to controlling the quantity and quality on construction sites, inspection can also prevent and reduce disability and serious damage in the future, thus further extending the lifetime of the building. This can also save the cost of building maintenance in the future other than ensure customer satisfaction. Inspection process should be practiced at all construction sites to ensure construction quality produce further developed and developing countries, and quality control.